Malaysia Economic Monitor, December 2020 : Sowing the Seeds - World Bank (World Bank, Washington, DC, 2020)
In 2020, the country experienced its sharpest recession in twenty years due to the impact of a triple shock related to the direct health impact of the pandemic; the economic impact of domestic restrictions on movement; and the impact of a synchronized global recession on Malaysia's tradeable sectors. Malaysia's economy is projected to grow by 6.7 percent in 2021, after contracting by 5.8 percent in 2020. However, the rebound in economic activity is subject to numerous uncertainties such as the deployment of an effective vaccine and the robustness of a rebound in global growth. Notwithstanding a growth rebound in 2021, Malaysia is not expected to recover fully from the shock of COVID-19 within the next few years. The Malaysian government has delivered a series of economic response packages to mitigate the impact of the crisis. Public policies, including cash transfers, wage subsidies and loan moratoria, have helped reduce the impact of the pandemic on vulnerable households and firms. While these measures have been vitally necessary, they have been implemented at a time when the government is experiencing a dramatic decline in revenues, creating a challenge to the medium-term fiscal outlook. Like governments across the world, Malaysia has depleted much of its available fiscal space and will exit the crisis with a larger burden of debt and contingent liabilities. This has resulted in difficult intertemporal constraints for the government to further expand expenditures on relief measures and consumption-supporting stimulus today, which may leave the government less equipped to invest in lasting recovery and growth tomorrow without the support of a stronger revenue base. When the current situation stabilizes and recovery becomes more entrenched, the government should refocus its fiscal policy to rebuild buffers against future shocks and to sustain public financing for inclusive, long-term growth. Addressing the fiscal legacies of the present crisis and the pre-existing structural weaknesses constraining the governments' ability to sustainably finance shared prosperity will require comprehensive medium-term plans to enhance revenue mobilization.